Critical Study Live Tilawah on TikTok by Taking Income According to Sharia - Khusna Hanifah; Salsa Bella Dewi Anggraeni; Miftahus Sa'adah; Fathimah Az Zahra; Sakinah Marhamah; Fatimah Az-Zahra; Syahidah Nur Hayati; Maryam Maryam; Febryan Hidayat (Walidem Institute and Publishing (WIP), 2024)
This study aims to find out the law of income from live recitation on TikTok from a sharia perspective. This research uses qualitative methods with a descriptive analysis approach to data from books and journals. It is known that the use of TikTok social media is very common in all circles with users reaching 1.5 billion. The existence of a live streaming feature that can provide income (commission) from viewers for creators (people who do live streaming) makes many people make TikTok a source of income. Some time ago, there was a phenomenon of live recitation of the Qur'an on TikTok, where content creators had the opportunity to earn income from such activities. In fact, in general, it is not permissible to take wages from the recitation of the Qur'an. The results concluded, that in Islamic law, there is no prohibition to receive commissions from work or activities that do not contain immoral elements. However, if the activity is related to worship, there is a difference of opinion among the scholars. After careful research and allusion (comparing similarities) with several tsars (sources) salaf with this issue, research succeeded in obtaining two laws in taking income from live recitation on TikTok, namely mubah if it aims to be for public interest or benefit, and haram if it aims to worship or get closer to Allah Subhanahu wa Ta'ala.